PENGARUH PROFITABILITAS, LIKUIDITAS, DAN TINGKAT PERTUMBUHAN TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR - Sari, Ni Putu Ayu Sinta Pradnya; Suryantini, Ni Putu Santi (E-Jurnal Manajemen; Vol 8 No 7 (2019)DO - 10.24843/EJMUNUD.2019.v08.i07.p20, 2019)
ABSTRACT This study aims to determine the effect of profitability, liquidity and growth rates on dividend policy. The research population was focused on manufacturing companies in the Indonesia Stock Exchange for the period 2013-2017, totaling 139 companies. Based on the sampling criteria with nonprobability sampling method with purposive sampling technique obtained a sample of 22 companies with a time of observation for 5 years, so that the number of observations obtained as many as 110 observations. The analysis technique used in this study is multiple linear regression analysis. The results of the analysis show that profitability and liquidity have a significant positive effect on dividend policy in manufacturing companies on the Indonesia Stock Exchange, while the growth rate has a significant negative effect on dividend policy in manufacturing companies on the Indonesia Stock Exchange. Keywords: Profitability, liquidity, growth rate, dividend policy